The influence of colour on the effect of advertising information - Lapė, Juvencijus; Masiliūnaitė, Lina (Psichologija, 2001)
The article offers the results of an experimental investigation into the influence of an advertising text of a notice on the turning of attention, the perception and the memorising of the text.The results of the investigation corroborate the hypothesis that the colour of advertising text influences the turning of attention, the perception and the memorising of the text. The red colour produces the greatest influence. The influence of the green colour is a little less significant. However the influence produced by the blue colour is two times weaker than the one made by the red colour. Though the red colour attracts attention better, subjects quote the text written in green more exhaustively. This indicates that the text written in green is read more attentively and willingly.
Keywords: influence of colour; advertising information